Severe acute toxicity following gemcitabine administration: A report of four cases with cytidine deaminase polymorphisms evaluation - Hryciuk, Beata (Oncol Lett, 2018)
Gemcitabine (GCB) is a pyrimidine antimetabolite widely used in various solid tumors as a single agent or as a component of multidrug regimens. In the majority of patients, GCB is well tolerated, however life-threatening complications occasionally occur. The current report presents four cases of severe acute toxicity, which included two that were fatal, following administration of GCB alone or in combination with cisplatin. Of the four cases, in one, a Naranjo Adverse Drug Reaction Probability Score was definite, in two, probable and in one possible. To determine the potential causes of these toxicities, polymorphic variants of cytidine deaminase, the primary enzyme involved in the hepatic metabolism of GCB, were assessed. The homogeneous c.435TT variant was detected in one patient and a heterozygotic c.435CT variant in two, one of whom additionally harbored a heterozygotic c.79AC variant.